2018
DOI: 10.1159/000491433
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 Prevents H<sub>2</sub>O<sub>2</sub>-Induced Apoptosis and Oxidative Stress in Human Lens Epithelial Cells via Inhibition of the NF-κB Signaling Pathway

Abstract: Aim: To investigate the regulation of microRNA-124 ­(miRNA-124) on NF-κB pathway from H2O2-induced apoptosis and oxidative stress in human lens epithelial cells (hLEC). Methods: The MTT (3-[4, 5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay was used to detect hLEC ­viability. HLECs were divided into Blank, H2O2, mimics (miRNA-124 mimics) + H2O2, NC+ H2O2, pyrrolidine dithiocarbamate (PDTC; NF-κB signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…40,41 Moreover, cataracts are directly related to the apoptosis of LECs caused by oxygen free radicals. 42,43 It has been reported that antioxidant genes and drugs can inhibit the oxidative damage caused by H 2 O 2 by reducing the activity of ROS. 44,45 Lens epithelial cells initiate apoptosis-related signal transduction pathways under oxidative stress, which mediates the apoptosis of LECs and promote the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Moreover, cataracts are directly related to the apoptosis of LECs caused by oxygen free radicals. 42,43 It has been reported that antioxidant genes and drugs can inhibit the oxidative damage caused by H 2 O 2 by reducing the activity of ROS. 44,45 Lens epithelial cells initiate apoptosis-related signal transduction pathways under oxidative stress, which mediates the apoptosis of LECs and promote the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in GSH-Px activity and exhaustion of GSH could increase injuries to the antioxidant system, ultimately resulting in lens epithelial cell apoptosis. Previous studies proposed that Bax, Bcl-2, and caspase-3 were related to the apoptotic process (Gu, 2018). Bax is a member of the Bcl-2 family that promotes apoptosis and increases in the Bax and Bcl-2 ratio promote cell apoptosis (Du et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miRNA-155 ameliorates high-glucose-induced endothelial injury by inhibiting NF-κB activation and promoting HO-1 and NO production [71]. Gu revealed that miRNA-124 prevents H 2 O 2 -induced oxidative stress and apoptosis in human lens epithelial cells by suppressing the activation of the NF-κB pathway [85]. Results of Wei et al indicated that NF-κB positively regulated miRNA-21 expression under oxidative stress, and programmed cell death protein 4 (PDCD4) was a direct target for miRNA-21 [86].…”
Section: Nf-κb Pathwaymentioning
confidence: 99%